2022
DOI: 10.3389/fpsyt.2022.896419
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes and associated factors among vaccinated and unvaccinated teachers against COVID-19 infection in Bangladesh

Abstract: BackgroundVaccination of teachers is recommended during the COVID-19 pandemic to reduce the risk of infection for themselves and their students, as well as to encourage their parents to get immunized. The present study investigated the mental health outcomes and associated factors among vaccinated and unvaccinated teachers against COVID-19 infection in Bangladesh.MethodsA cross-sectional survey was conducted in Bangladesh from March 4 to September 9, 2021. The frequency of symptoms of psychological distress, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…This could have helped to alleviate anxiety among the population. A study found that vaccinated participants in Bangladesh were protective against developing any mental illness [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could have helped to alleviate anxiety among the population. A study found that vaccinated participants in Bangladesh were protective against developing any mental illness [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The author used the Japanese version of the GHQ-12, which was developed by Nakagawa and Daibou (2013). The GHQ, developed by Goldberg and Williams (1998) has been commonly used to screen for anxiety and depression in COVID-19-related studies (e.g., Kostić et al, 2021;Silva et al, 2021;Alam et al, 2022). The scale comprises 12 items relating to physical and mental conditions experienced in the preceding week.…”
Section: General Health Questionnaire (Ghq)mentioning
confidence: 99%
“…Studies involving 1257 teachers in Bangladesh, 453,167 people in the United States, 4244 in China, and 304 in Turkey demonstrated that those who had received the vaccine had a lower prevalence of stress, depression, anxiety, post-traumatic stress disorder, insomnia, and fear symptoms. [23][24][25][26] People who feel more at risk of being infected with COVID-19 are likely to get vaccinated. 23 Unfortunately, this study was not observed.…”
Section: Association Between Psychological Status and Spiritual Activ...mentioning
confidence: 99%
“…[23][24][25][26] People who feel more at risk of being infected with COVID-19 are likely to get vaccinated. 23 Unfortunately, this study was not observed.…”
Section: Association Between Psychological Status and Spiritual Activ...mentioning
confidence: 99%